Membangun Karakter Antikorupsi pada Siswa SMK Negeri 3 Kota Cimahi : (Edukasi Dampak Berbagai Perilaku Koruptif di Sekolah) - Halimah, Lili; Fajar, Arnie; Heni Heryani, Heni Heryani (Forum Komunikasi Dosen, 2024)
All elements of society of course really hope for prosperity and the culture of corruption is certainly one of the threats to achieving that prosperity. The easiest and most effective effort to eradicate corruption is to instill the values ​​of integrity in the younger generation. The younger generation has sufficient knowledge about corruption and anti-corruption behavior. This means that there is a weakness in the younger generation regarding awareness of developing an anti-corruption culture within themselves, so it can be concluded that anti-corruption education is needed for the younger generation in order to help grow their legal awareness. In this way, our team of lecturers and students held counseling with students at Cimahi City State Vocational High School 3 to provide understanding to the younger generation about corrupt behavior in our daily lives which we often accidentally do, and which has an impact on our future lives when we are adults. This outreach is intended to make the younger generation aware that corrupt behavior is a source of disaster for the nation's future. The younger generation is a milestone in implementing changes in a nation. The young generation with all its idealism can break the chain of corruption if it is equipped from an early age with an anti-corruption mentality which can be obtained through anti-corruption education.